PERANCANGAN E-PRESENSI GURU BERBASIS APPSHEET PADA SD ISLAM TERPADU AL BANIN KOTA MAKASSAR - Ahmad Radif Ridhawi; Iwan Suhardi; Maya Sari Wahyuni (STKIP Subang, 2026)
This research aims to design an AppSheet-based teacher e-attendance system to be implemented as a replacement for the manual attendance system at SD Islam Terpadu Al Banin, Makassar City. The background of this research is formed from the problem of teacher attendance administration which is still carried out manually, resulting in delays in recapitulation, risk of data loss, and inefficiency in attendance management. The type of this research is software engineering research using the Waterfall development model. This AppSheet is designed with no-code integrated with Google Sheets as the database. The research data were obtained through observation and interviews as well as system testing by referring to application quality standards using ISO 25010 which includes aspects of functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. The results show that the system has a 100% success rate in functional suitability and usability is categorized as very feasible. The system also shows stable performance in the aspect of reliability, is compatible on various browsers (compatibility), meets maintainability indicators, runs well on various platforms (portability), has good performance based on PageSpeed Insights, and is declared very secure (security) through Virustotal testing. The results of the study show that the AppSheet-based e-attendance system has functioned properly according to user needs. Teachers can perform check-in, check-out, and submit leave requests digitally with ease. Attendance data will be automatically stored in Google Sheets which can be accessed by the admin in real-time. The validation results show that the application has a high level of ease of use, efficiency, and security. In addition, the system can also be used on all devices. This AppSheet-based e-attendance application can improve school administrative efficiency and support the digitalization of teacher attendance data management in the school environment.